MEMOTIVASI PERILAKU HEMAT ENERGI DAN RAMAH LINGKUNGAN DI SEBUAH HOTEL - G. Santika, Wayan (Bumi Lestari, 2013)
Abstrak The present study aimed to find out whether persuasive messages with descriptive norms and norms of reciprocation were better than the standard message in increasing participation in hotel’s reuse linens and towels program and to know whether similar studies conducted in the individualistic culture of the United States could be replicated for the Indonesian collectivistic culture. The study started by printing four different cards with standard, standard with bigger fonts, descriptive norms, and norms of reciprocation messages. Cards were placed in rooms of a hotel located in Bali. Results show that cards printed with descriptive norms and norms of reciprocation messages were indeed more dominant than the standard one in increasing participation in linens and towels reuse program. The results were similar to those conducted in the United States.
Keywords: Kata kunci: towels reuse program, norma deskriptif, norma resiprokatif, linen